Solve for x y=cx+N

Math
y=cx+N
Rewrite the equation as cx+N=y.
cx+N=y
Subtract N from both sides of the equation.
cx=y-N
Divide each term by c and simplify.
Tap for more steps…
Divide each term in cx=y-N by c.
cxc=yc+-Nc
Cancel the common factor of c.
Tap for more steps…
Cancel the common factor.
cxc=yc+-Nc
Divide x by 1.
x=yc+-Nc
x=yc+-Nc
Move the negative in front of the fraction.
x=yc-Nc
x=yc-Nc
Solve for x y=cx+N

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top